2011
DOI: 10.1021/pr200352m
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Biomarkers of Prenatal Disorders: An Exploratory NMR Metabonomics Study of Second Trimester Maternal Urine and Blood Plasma

Abstract: This work describes an exploratory NMR metabonomic study of second trimester maternal urine and plasma, in an attempt to characterize the metabolic changes underlying prenatal disorders and identify possible early biomarkers. Fetal malformations have the strongest metabolic impact in both biofluids, suggesting effects due to hypoxia (leading to hypoxanthine increased excretion) and a need for enhanced gluconeogenesis, with higher ketone bodies (acetone and 3-hydroxybutyric acid) production and TCA cycle demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 46 publications
15
145
2
Order By: Relevance
“…In paper I, even with the small sample size, reproducible results could be found compared to similar studies. 77,142,201 In paper II, although there were relatively few hypertensive cases, the large number of normotensive pregnancies established a robust baseline to which the hypertensive groups could be compared. Sample collection is labor intensive and it is di cult to obtain su cient samples for high powered metabolomic studies.…”
Section: Multivariate Analysesmentioning
confidence: 99%
“…In paper I, even with the small sample size, reproducible results could be found compared to similar studies. 77,142,201 In paper II, although there were relatively few hypertensive cases, the large number of normotensive pregnancies established a robust baseline to which the hypertensive groups could be compared. Sample collection is labor intensive and it is di cult to obtain su cient samples for high powered metabolomic studies.…”
Section: Multivariate Analysesmentioning
confidence: 99%
“…The increase in urinary excretion of the ketone body 3-HB in MD could suggest an increase in fatty acid oxidation (FAO) (41). FAO is indispensable for the conversion of lipids (dietary or from lipid storage) to ketone bodies (42).…”
Section: Metabolites From Protein Lipid and Carbohydrate Metabolic Pmentioning
confidence: 99%
“…However, the reasons for these changes in metabolic process relating to the metabolism of pregnant mother are still not well understood. Conventional clinical pregnancy monitoring mainly rely on routine physical and histological examinations (Diaz et al, 2011;Halscott et al, 2014;Hourrier et al, 2010;Legardeur et al, 2011). These examinations such as ultrasound testing are often carried out in combination with chorionic villus sampling, amniocentesis, and cordocentesis, as well as the measurement of specific maternal serum markers for chromosomal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the analysis of biological fluids or tissues has been used successfully in identification of typical compounds of various physiologic or pathologic conditions by providing the underlying metabolic changes during the pregnancy period, and a steady inflow of research development has been reported in this context by using maternal blood and urine, amniotic fluid, and umbilical cord blood to characterized the relevant prenatal diseases such as preeclampsia (Austdal et al, 2014;Luque et al, 2014;Redman and Sargent, 2005), fetal malformations (Diaz et al, 2011), gestational diabetes mellitus (Bo et al, 2015;Hernandez et al, 2014), poor pregnancy outcome (Halscott et al, 2014;Hourrier et al, 2010), preterm delivery (Alexandre- Gouabau et al, 2013) and small for the gestational age (Cohn et al, 2010). Moreover, protein and nitrogen metabolism were found to play extremely important roles in pregnancy and the development of the fetus (Altobelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%